2021
DOI: 10.1080/2331186x.2021.1978623
|View full text |Cite
|
Sign up to set email alerts
|

Translation and content validation of the trans-contextual model questionnaire battery and development of a web-based version for 10-to 12-year-old Danish schoolchildren

Abstract: His research area is sport psychology, football and motivation, which will be applied within the "11 for Health -in Denmark" concept. The "11 for Health -in Denmark" concept is a health education concept targeted towards 10-12-year-old schoolchildren, taking place on the football pitch. The authors have previously investigated the impacts of the "11 for Health -in Denmark" concept and found positive effects on schoolchildren's physical fitness, cognitive performance, well-being, enjoyment and health knowledge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 54 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Details of the TCM questionnaire used in this study and validated by Madsen et al, 12 are summarized below and full details can be found in Appendix S1B. In the absence of actual observations on how teachers support autonomous motivation in the class, schoolchildren's perceived autonomy support by PE teachers were used 21 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of the TCM questionnaire used in this study and validated by Madsen et al, 12 are summarized below and full details can be found in Appendix S1B. In the absence of actual observations on how teachers support autonomous motivation in the class, schoolchildren's perceived autonomy support by PE teachers were used 21 .…”
Section: Methodsmentioning
confidence: 99%
“…24,29 Face and content validity of the TCM constructs for a specific 57-item 3-wave web-based questionnaire to be used in the program has been established in Danish schoolchildren. 12 Applying the TCM to the program, is considered to help understand if school-based football is motivating as stated in the literature, 8,22 and if the activities can enhance motivation and intentions to participate in out-of-school PA. Therefore, this study aimed to examine the processes by which 10-to 12-year-old schoolchildren's perceived autonomy support by their teacher and autonomous motivation related to autonomous motivation, beliefs, intentions, and actual behavior.…”
Section: The Trans-contextual Modelmentioning
confidence: 99%
See 3 more Smart Citations